M23 - GENETIC ASSOCIATION AND FUNCTIONAL CHARACTERIZATION OF A VARIANT IN THE MCPH1 GENE IN BIPOLAR DISORDER AND SCHIZOPHRENIA - Aleissa, Mariam; Sharp, Sally; Fiorentino, Alessia; O'Brien, Niamh; Bass, Nicholas; Curtis, David; McQuillin, Andrew (European neuropsychopharmacology, 2019)
Both Schizophrenia (SCZ) and Bipolar Disorder (BPD) disorder are serious psychiatric conditions that can give rise to debilitating symptoms that can severely impact the life of the affected individual, and their families. We have previously reported that the MCPH1 gene variant rs61749465 A>G (p.Asp61Gly) showed suggestive evidence for association with schizophrenia (SCZ; Leonenko et al. 2017). The MCPH1 gene has multiple roles in cellular functions including, DNA damage/repair pathways; centrosomal localization; E2F transcription factor 1-mediated apoptosis; transcriptional activation of cell cycle checkpoint, DNA stability; and telomere structure. A second MCPH1 point mutation (rs199422124 C>G; p.Thr27Arg) is an autosomal recessive cause of microcephaly. The schizophrenia associated MCPH1 variant rs61749465 was tested for association in 2,300 Bipolar Disorder (BPD) subjects, and 1,820 normal comparison subjects. We also analysed the microcephaly causing mutation rs199422124 in the BPD and control subjects and in our SCZ cohort of 1,930 subjects. Next, we conducted analysis of the in vitro effects of the rs6174965 and rs199422124 variants on cell survival/proliferation using cell counts, and the MTT assay; their effect on DNA damage using the comet assay; their effect on mRNA stability using a combination of Actinomycin D treatment followed by Q-PCR; and their effect on gene expression using RNA-Seq analysis combined with pathway analysis and gene network analyses. After genotyping we report evidence for association with BPD (P=0.0009). Notably the variant allele of rs61749465 was absent in the 1,820 comparison subjects tested. rs61749465 is located in the N-terminal of the BRCT1 domain of MCPH1. Bioinformatic analysis predicted the Asp61Gly substitution to be damaging to MCPH1 protein function. rs199422124 was not detected in any of the participants. We sought to characterize the functional effects of these variants on MCPH1 function. Cell viability and cell count assays indicated that the variant allele of rs199422124 had a larger impact on cell survival compared to the variant allele of rs61749465, however neither of the variant alleles significantly altered DNA damage or mRNA stability. Gene expression analysis for rs61749465 using RNA-seq shows that the expression of a number of heat shock protein have been affected. Gene network and pathway analysis indicated that the variant alleles may impact cellular aging and protein translation. Further in vitro and in vivo characterization of the rs61749465 variant in MCPH1 may provide insight into the molecular pathogenesis of psychosis.